The Effectiveness of Monetary Policy in Driving Economic Growth - Agika Ayla Sari Dewi Bangun; Sanusi Gazali Pane; Teresia Dakhi; Dermawan Syah Putra Nehe; Regina Roswita Zai (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of monetary policy in stimulating economic growth. Monetary policy, through instruments such as interest rates, money supply, and banking credit, plays a strategic role in influencing real economic activities. The research method employs a conceptual approach and a literature review, examining monetary economic theories and relevant previous research findings from both national and international literature. The analysis is conducted by tracing the transmission mechanisms of monetary policy on economic growth through interest rate channels, investment, consumption, and exchange rate stability. The expected results of this study indicate that monetary policy managed credibly and responsively to macroeconomic conditions is capable of fostering sustainable economic growth. A reduction in interest rates is expected to increase investment and consumption, while the control of the money supply can maintain inflation stability, thereby creating a conducive economic climate for growth. This research is expected to provide a theoretical contribution to enriching the study of monetary economics and serve as a reference for formulating effective monetary policies to support economic growth.